Lumbar disc herniation surgery in adolescents and young adults: a long-term outcome comparison. (November 2019) - Lagerbäck, Tobias; Möller, Hans; Gerdhem, Paul
Abstract : Aims: The purpose of this study was to investigate the risk of additional surgery in the lumbar spine and to describe long-term changes in patient-reported outcomes after surgery for lumbar disc herniation in adolescents and young adults. Patients and Methods: We conducted a retrospective study design on prospectively collected data from a national quality register. The 4537 patients were divided into two groups: adolescents (≤ 18 years old, n = 151) and young adults (19 to 39 years old, n = 4386). The risk of additional lumbar spine surgery was surveyed for a mean of 11.4 years (6.0 to 19.3) in all 4537 patients. Long-term patient-reported outcomes were available at a mean of 7.2 years (5.0 to 10.0) in up to 2716 patients and included satisfaction, global assessment for leg and back pain, Oswestry Disability Index, visual analogue scale for leg and back pain, EuroQol five-dimension questionnaire (EQ-5D), and 36-Item Short-Form Health Survey (SF-36) Mental Component Summary and Physical Component Summary scores. Statistical analyses were performed with Cox proportional hazard regression, chi-squared test, McNemar's test, Welch–Satterthwaite t -test, and Wilcoxon's signed-rank test. Results: Any type of additional lumbar spine surgery was seen in 796 patients (18%). Surgery for lumbar disc herniation accounted for more than half of the additional surgeries. The risk of any additional surgery was 0.9 (95% confidence interval (CI) 0.6 to 1.4) and the risk of additional lumbar disc herniation surgery was 1.0 (0.6 to 1.7) in adolescents compared with the young adult group. Both age groups improved their patient-reported outcome data after surgery (all p < 0.001). Changes between short- (mean 1.9 years (1.0 to 2.0)) and long-term follow-up (mean 7.2 years (5.0 to 10.0)) were small. Conclusion: The risk of any additional lumbar spine surgery and additional lumbar disc herniation surgery was similar in adolescents and young adults. All patient-reported outcomes improved from preoperative to the short-term follow-up, while no likely clinically important differences between the short- and long-term follow-up were seen within both groups. Cite this article: Bone Joint J 2019;101-B:1534–1541